2003
DOI: 10.1071/zo03034
|View full text |Cite
|
Sign up to set email alerts
|

Breeding behaviour and ecology of the sexually size-dimorphic brown songlark, Cinclorhamphus cruralis

Abstract: The Australian endemic brown songlark, Cinclorhamphus cruralis, is one of the most sexually size-dimorphic of all birds, and yet its breeding ecology remains poorly documented. Here we redress this situation by describing the breeding activities of brown songlarks over three years (1998)(1999)(2000) in the semi-arid grasslands of south-western New South Wales. Study populations of this nomadic species were selected in late August of each year on the basis of high adult abundance. Adult males at these sites wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Owens and Hartley (1998) indicated that species, like Carolina Wrens, that are socially and genetically monogamous, and show little sexual difference in parental care, are less sexually dimorphic than species with more intense sexual selection such as polygamous species or species where individuals engage in mixed reproductive strategies (e.g., see Magrath et al 2003). The degree of SSD in Carolina Wrens is less than in polygamous species, and my results suggest possible causations and directions for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Owens and Hartley (1998) indicated that species, like Carolina Wrens, that are socially and genetically monogamous, and show little sexual difference in parental care, are less sexually dimorphic than species with more intense sexual selection such as polygamous species or species where individuals engage in mixed reproductive strategies (e.g., see Magrath et al 2003). The degree of SSD in Carolina Wrens is less than in polygamous species, and my results suggest possible causations and directions for future work.…”
Section: Discussionmentioning
confidence: 99%
“…During the nestling period, broods received a range of invertebrate prey items that were provided almost exclusively by the female. Male adults were observed feeding at just four of 66 broods (6%), and at these four nests contributed an average of only 18% of feeds (Magrath et al . 2003a).…”
Section: Resultsmentioning
confidence: 99%
“…2003a). Mothers were observed feeding young of both sexes for up to 3 weeks after they left the nest (Magrath et al . 2003a), but the data were too few to determine if the time to independence differed between the sexes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations